Os professores de matemática e a geometria: opiniões sobre a área e seu ensino. - Crescenti, Eliane Portalone (2005)
Based on the professional experience with the Geometry teaching and on the existing bibliography which is approaching the abandon of Geometry and its teaching, the possible causes of this abandon and the importance of its teaching as well as its ransom in the Mathematics classes appeared disquietude which originated the present research, of which objective constitutes in knowing how the Geometry teaching developed in the 5ths 8ths grades of the Elementary School (Ensino Fundamental) and what the Mathematics teachers thought about Geometry and its teaching. Being so, the focus of this research was teachers, professionals whose voices must be heard in order to understand the school reality better. The data collecting involved interviewing nine Mathematics teachers with different years of experience and the methodological foundation of our work was based on their narratives. Their narratives showed that they have some lack of autonomy as well as precarious knowledge of the importance of the Geometry contents. The justification of the more experienced teachers did not differ from the ones placed by the less experienced teachers, being the less experienced teachers very attached to the bureaucratic organization and basing themselves more on the didactic books. More emphasis in the Geometry teaching was noticed among the more experienced teachers and these teachers were more successful and more respected by the students, although their practices were closer to the traditional teaching. The resources used by two of the less experienced teachers were closer to the more modern pedagogical approaches. We have also noticed, in general, that the educational programs basic or continuing education have not backrested the educational practices with the Geometry teaching and that in the school there isn t support for this developing either. On the other hand, to work with narratives turned possible to know the teacher practice better, in order to indicate subsidies to the present situation of the Geometry teaching to improve that situation.